2016
DOI: 10.3892/ol.2016.5406
|View full text |Cite
|
Sign up to set email alerts
|

Role of Annexin A2 in the EGF-induced epithelial-mesenchymal transition in human CaSki cells

Abstract: Abstract. The epidermal growth factor receptor (EGF-R) signaling pathway is thought to have an important role in the development and progression of several carcinomas, as it is associated with cell proliferation, differentiation and migration. Activation of EGF-R signaling regulates epithelial-mesenchymal transition (EMT)-associated invasion and migration in normal and malignant epithelial cells. However, the specific mechanisms have not yet been fully elucidated. The present study utilized wound healing assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Furthermore, ANXA2 depletion significantly reduced cell invasion and metastatic potential of breast cancer model in vivo. Similar findings of EGF enhanced ANXA2 expression and EMT promotion were observed in cervical cancer, pancreatic cancer and colon cancer cell lines (19,27,28).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, ANXA2 depletion significantly reduced cell invasion and metastatic potential of breast cancer model in vivo. Similar findings of EGF enhanced ANXA2 expression and EMT promotion were observed in cervical cancer, pancreatic cancer and colon cancer cell lines (19,27,28).…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we hypothesized that there is a correlation between tumor and stromal ANXA2 expression in the presence of detectable CTCs. Moreover, we hypothesized, that the expression of ANXA2 on CTCs might be responsible for previously-observed coagulation activation (19).…”
mentioning
confidence: 99%
“…Implicated in signaling transduction, phosphorylated Anxa2 at Tyr23 binds to STAT3 and promotes its phosphorylation at Tyr705 as well as following dimerization and nuclear translocation, resulting in up-regulated MMPs and enhanced EMT [38,39]. In addition, couple of researches have demonstrated Anxa2 content is correlated to cell migration capability [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that overexpressed Smad3 and SETDB1 can bind coordinately to the promoter of ANXA2 , which encodes a calcium‐dependent, phospholipid‐binding protein involved in actin polymerization, and that SETDB1 represses ANXA2 expression . Recently, ANXA2 expression was reported to contribute to EMT , raising the possibility that SETDB1 can control the level of Smad3‐mediated activation of several genes that promote EMT. Therefore, the attenuation of SETDB1 expression during EMT may facilitate the transdifferentiation process and help stabilize the mesenchymal phenotype through its effects on several genes, including Snai1 and Anxa2 .…”
Section: Discussionmentioning
confidence: 99%